Absorption Difference Spectroscopy of Lysozyme with Nd(III) in Presence of Zn(II), Cd(II), Ca(II) and Mg(II) Involving 4f-4f Transition - Mehta, S.B.; Shah, M.K. (Asian Journal of Chemistry, 2010)
The absorption difference and comparative absorption spectrophotometry of neodymium(III) with lysozyme at different pH (2,4,6) in different solvents such as methanol, dimethylformamide, acetonitrile and t-butanol in presence and and absence of chemically different metal ions like Ca(II) and Mg(II) on one hand as well as Zn(II) and Cd(II) on the other hand have shown that the binding capacity of lysozyme is better at pH 2 than that observed at pH 4 and 6, because lysozyme has been known to exhibit biological activities in the mildly acidic medium while the higher range of pH does not contribute remarkably towards binding. Among different solvent compositions maximum intensification takes place when solvent comprises of DMF and MeOH. Acetonitrile causes very minor and t-BuOH leads to a very small variation. The effect of hard metal ions like Ca(II) and Mg(II) on hetero metal compositions of Nd(III)-lysozyme results in lowering of the intensities of 4f-4f bands of Nd(III) ions. As Ca(II) and Mg(II) both are hard metal ions like Nd(III), hence they enjoy identical binding atom preference and therefore compete effectively for lysozyme identical coordinating sites. Contrary to these, Cd(II) and Zn(II) both being soft metal acceptors, they prefer soft donor site of lysozyme and stimulate the binding of Nd(III) to lysozyme.